LEGAL CONSEQUENCES OF ISSUING ELECTRONIC LAND CERTIFICATES AND THEIR LEGAL FORCE BASED ON THE REGULATION OF THE MINISTER OF AGRARIAN AND SPATIAL PLANNING / HEAD OF THE NATIONAL LAND AGENCY OF THE REPUBLIC OF INDONESIA NUMBER 3 OF 2023 CONCERNING ISSUING E - Hafiddin, Arya; Wibisono, Krisna Tri Prasetyo; Basharahil, Mohammad Faris; Isra, Muhammad Ibnu; Hekmatiar, Sabiyan Yudhistira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Land certificates provide important meaning and benefits for rights holders who, if there is a dispute over the land, can be a guarantee of legal certainty. The rapid technological advances that have occurred in this digitalization era have made the government issue an electronic land certificate policy, which has become a pro and con for the community. The community still questions the guarantee of security with the implementation of this electronic land certificate. Electronic certificates and physical land certificates have the same legal force. The choice of certificate type depends on the needs and preferences of each individual . Both are valid evidence of land ownership in Indonesia regulated in Law Number 5 of 1960 concerning Agrarian Principles (UUPA) , Government Regulation Number 24 of 1997 concerning Land Registration , Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration , Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration .